49th IEEE Conference on Decision and Control (CDC) 2010
DOI: 10.1109/cdc.2010.5717260
|View full text |Cite
|
Sign up to set email alerts
|

Indirect training of a spiking neural network for flight control via spike-timing-dependent synaptic plasticity

Abstract: Recently, spiking neural networks (SNNs) have been shown capable of approximating the dynamics of biological neuronal networks, and of being trainable by biologicallyplausible learning mechanisms, such as spike-timing-dependent synaptic plasticity. Numerical simulations also support the possibility that they may possess universal function approximation abilities. However the effectiveness of training algorithms to date is far inferior to those of other artificial neural networks. Moreover, they rely on directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In [15], the authors proposed an indirect training method based on a Poison spike model and demonstrated it on a network of Izhikevich neurons. In this work it was found that the adaptive critic architecture described in Section 3 could be implemented without modeling the neuron response in closed form.…”
Section: Models Of Neuron and Synapse Various Models Of Snnsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [15], the authors proposed an indirect training method based on a Poison spike model and demonstrated it on a network of Izhikevich neurons. In this work it was found that the adaptive critic architecture described in Section 3 could be implemented without modeling the neuron response in closed form.…”
Section: Models Of Neuron and Synapse Various Models Of Snnsmentioning
confidence: 99%
“…In this work it was found that the adaptive critic architecture described in Section 3 could be implemented without modeling the neuron response in closed form. However, the effectiveness of the approach in [15] was limited in that, due to the use of a stochastic Poison model, the Izhikevich SNN could not converge to the optimal control law. Therefore, in this paper, a new deterministic spike model is proposed and implemented by deriving the training equations in closed form, using a leaky integrate-and-fire (LIF) SNN.…”
Section: Models Of Neuron and Synapse Various Models Of Snnsmentioning
confidence: 99%
See 3 more Smart Citations